Watching over her : a novel - Andrea, Jean-Baptiste, 1971- (Simon & Schuster, 2026)
"In an Italian monastery, a sculptor named Mimo lays on his deathbed. For decades, he has lived among the monks who watch over his masterpiece, an arresting statue that haunts all who see it. During his final hours, he reveals his life story: his impoverished childhood, brutal apprenticeship, and, most important, his meeting with Viola Orsini, the only daughter of a powerful and dangerous aristocratic family. Mimo and Viola are instantly drawn to one another, viewing themselves as outsiders--Mimo, for his dwarfism, Viola for her ability to remember everything she has ever read or experienced. Together, they traverse the unrest of the twentieth century, from the rise of fascism to the violence of the world wars. While Mimo becomes a celebrated artist, Viola chases her own dreams of becoming an emancipated woman. Over the decades, they will lose and find each other time and again, but never will they give up on the love they share"--